Persistence with pharmacological treatment in the specialist mental healthcare of patients with severe mental disorders. - Conti, V; Lora, A; Cipriani, A; Fortino, I; Merlino, L; Barbui, C (2012)
PURPOSE: The aim of this study was to measure persistence with pharmacological treatment in the specialist mental healthcare of patients with schizophrenia, bipolar disorder, and unipolar depression in Lombardy, a region of 10 million inhabitants located in the northernmost part of Italy. METHODS: The data concerning psychiatric care used in this study were retrieved from the regional Psychiatric Information System, while information on drug treatment was retrieved from the regional administrative database. Time to lack of persistence with initial pharmacological treatment was the outcome measure. RESULTS: A total of 11,797 patients, followed in the specialist mental healthcare system, started a new pharmacological treatment for depression, schizophrenia, or bipolar disorder during 2007. Overall, 8,500 patients (72.1%) discontinued treatment during the 12 month follow-up, with a median duration of 101 days. Very similar discontinuation rates were observed in patients with unipolar depression, schizophrenia, and bipolar disorder. In the multivariate analysis, operational definitions of continuity and intensity of care were the most robust determinants of persistence with drug treatment in each of the three cohorts of psychiatric diagnoses. CONCLUSIONS: High rates of treatment discontinuation were found in a population of patients with severe mental disorders followed in the specialist mental healthcare system of an Italian region, with no differences among patients with unipolar major depression, schizophrenia, and bipolar disorder. These findings corroborate the notion that the problem of treatment discontinuation in psychiatric disorders is a factor related to the capacity of the mental health system to assure and maintain continuity and intensity of care.